Multimorbidity and mortality thereof, among non-western refugees and family reunification immigrants in Denmark - a register based cohort study - Nasim Taleshan; Jorgen Holm Petersen; Michaela Louise Schioetz; Helle Gybel Juul-Larsen; Marie Norredam (BMC, 2018)
Abstract Background The prevalence of multimorbidity, defined by having two or more chronic diseases, is increasing in many Western countries. Simultaneously, the migrant population in Western countries has increased, making up a growing proportion of European populations. This study aims i) to determine the quantity and quality of multimorbidity patterns among refugees and family reunification immigrants from non-Western countries compared to Danish-born, and ii) to compare the mortality burden among those with multimorbidity in the two groups. Methods Through the Danish Immigration Service, we conducted a historically prospective cohort study. We identified a total of 101,894 adult migrants who were sub-categorised into refugees and family reunification immigrants, and matched them to a Danish-born comparison group 1:6 on age and sex. Through the Danish National Patient Registry, we obtained information on all in- and outpatient data on hospitalised and ambulatory patients. To assess multimorbidity we used Charlson Comorbidity Index based on ICD-10 codes, together with ICD-10 diagnostic categories for psychiatric disease. We used Cox regression analysis to calculate risk of multimorbidity and risk of mortality in people with multimorbidity. Results Overall refugees had higher risk of multimorbidity compared to Danish-born, while family reunification immigrants had a lower risk. When adjusting for civil status and mean income, the risk was lower for all migrant groups compared to Danish-born. Risk of mortality in people with multimorbidity, was lower for all migrant groups, compared to Danish-born. Conclusion Refugees are an at-risk group for multimorbidity, however, mortality among those with multimorbidity is lower in all migrant groups compared to Danish-born.